The Past, Love, Money, and Much More: Philippines-Japan Relations Since the End of the Second World War. - Tigno, Jorge V. (Philippine Social Sciences Review; Vol 62 No 1: January-June 2010, Ed. Eric Manalastas, 2011)
Lydia N. Yu Jose (Editor). (2008). The Past, Love, Money, and Much More: Philippines-Japan Relations Since the End of the Second World War. Quezon City: Ateneo de Manila University Press.